THE SECTION CLEMENSIA OF CHISOCHETON (MELIACEAE) - M. Jacobs (Research Center for Biology, 1955)
Clemensia Merr.is considered a section of Chisocheton Bl.Two species are distinguished and described, Chisocheton medusae f.hiascens Jacobs is published as a new form.